Effect of irrigation and fertilization on crop yield and fruit quality of the Tahiti lime Citrus latifolia Tanaka (Rutaceae) (2015)
In a seven years old citrus grove of Tahiti lime Citrus latifolia Tanaka (Rutaceae) located in El Espinal, Tolima,Colombia, which has a predominantly negative water balance throughout the year, we evaluated the effect of irrigation and fertilization on yield and fruit quality in 2009 and 2011. Trees were subjected to three levels of water based on the evapotranspiration reference (ETo):L1=100 %, L2=70 % and L3=50 %. We applied three nitrogen treatments: N1=nitrogen required by the nutritional balance, N2=twice the level of nitrogen used in N1, and N3=fertilizer application used by the common farmer. We evaluated the performance, fruit weight, polar and equatorial diameter of fruit, shell thickness, weight and percentage of juice, acidity, soluble solids and vitamin C. The experiment was conducted under a randomized complete block design in a split plot arrangement; the variance and means of the data were statistically analyzed with SAS. And optimal response is between irrigation and fruit quality interaction was obtained with irrigation L1 and fertilization N2. We obtained the highest values in the response variables when the highest amount of water was applied L1,regardless of fertilizer applications, indicating that a lower water supply not only affects the performance of the plant, but also the quality of the fruit, minimizing market opportunities